A Case of Eosinophilic Granulomatosis with Polyangiitis (Churg-Strauss, EGPA) Presenting With Relapsed Mononeuritis Multiplex - BA, Hilmi; MM, Ainon (IIUM Medical Journal Malaysia, 2014)
We report a case of eosinophilic granulomatosis with polyangiitis (EGPA), a rare multisystem disorder characterized by difficult-to-control asthma, hypereosinophilia and polyneuropathy. We also discuss the Five Factor Score (FFS) risk stratification strategy, which is used to quantitate the extent of the disease and guide treatment strategy.